Cerebrospinal fluid pressure and glaucoma: regulation of trans-lamina cribrosa pressure. Issue 6 (4th December 2013) - Marek, Brian; Harris, Alon; Kanakamedala, Priyanka; Lee, Eric; Amireskandari, Annahita; Carichino, Lucia; Guidoboni, Giovanna; Tobe, Leslie Abrams; Siesky, Brent
Abstract : Increased trans-lamina cribrosa pressure difference (TLCPD), the difference of intraocular pressure (IOP) and orbital cerebrospinal fluid pressure (CSF-P), has been investigated as a possible risk factor in glaucoma pathogenesis. In fact, lower CSF-P in the setting of normal IOP has been implicated as a potential risk factor for normal tension glaucoma. Increased TLCPD has been associated with decreased neuroretinal rim area and increased visual field defects. Furthermore, dysregulation of systemic blood pressure has been associated with changes in IOP. Recent studies have also suggested that increased body mass index (BMI) is associated with decreased prevalence of glaucoma, which may be due to an increased CSF-P with increased BMI found in many studies. Given the interaction of various pressures, their role in glaucoma pathophysiology has come under investigation and warrants further study in order to better understand the aetiology and progression of glaucoma.